2009
DOI: 10.1152/ajpheart.01133.2008
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human activated protein C improves endotoxemia-induced endothelial dysfunction: a blood-free model in isolated mouse arteries

Abstract: Recombinant human activated protein C (rhAPC) is one of the treatment panels for improving vascular dysfunction in septic patients. In a previous study, we reported that rhAPC treatment in rat endotoxemia improved vascular reactivity, although the mechanisms involved are still under debate. In the present study, we hypothesized that rhAPC may improve arterial dysfunction through its nonanticoagulant properties. Ten hours after injection of LPS in mice (50 mg/kg ip), aortic rings and mesenteric arteries were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…But in rodent models of endotoxemia, rhAPC also demonstrated a protective effect on microcirculation through the inhibition of leukocyte-endothelial interaction, inhibition of subsequent leukocytes adherence to the endothelium and suppression of inflammatory cytokine production [115][116][117]. Moreover, Sennoun et al [69] reported that rhAPC improved both endothelial dysfunction and arterial contractility induced by bacterial LPS in isolated mouse arteries, through an increase in eNOS activation, a reduction of LPS-induced upregulation of NF-B and iNOS expression. At last, De Backer et al [118] used OPS to visualize sublingual microcirculation and investigate the effects of rhAPC on septic patients; they showed an early increase of perfused capillaries.…”
Section: Recombinant Human Activated Protein Cmentioning
confidence: 99%
“…But in rodent models of endotoxemia, rhAPC also demonstrated a protective effect on microcirculation through the inhibition of leukocyte-endothelial interaction, inhibition of subsequent leukocytes adherence to the endothelium and suppression of inflammatory cytokine production [115][116][117]. Moreover, Sennoun et al [69] reported that rhAPC improved both endothelial dysfunction and arterial contractility induced by bacterial LPS in isolated mouse arteries, through an increase in eNOS activation, a reduction of LPS-induced upregulation of NF-B and iNOS expression. At last, De Backer et al [118] used OPS to visualize sublingual microcirculation and investigate the effects of rhAPC on septic patients; they showed an early increase of perfused capillaries.…”
Section: Recombinant Human Activated Protein Cmentioning
confidence: 99%
“…During sepsis, the endothelial function is altered and the endothelial surface becomes proadhesive, procoagulant and antifibrinolytic [42]. The endothelium is one of the primary targets of circulating MPs, as demonstrated by Barry and colleagues [43] in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Vascular reactivity of aortic rings was studied on a wire myograph (Danish Myo Technology, Aarhus, Denmark) as described previously [22] and in the ESM.…”
Section: Vascular Reactivitymentioning
confidence: 99%
“…Interestingly, APC and Dexa overcome the deleterious endothelial effect of CLP. Indeed, the beneficial effect of APC and Dexa on ACh-induced relaxation could be explained by eNOS activation and COX vasorelaxant metabolites [22]. NO is one of the major endothelial relaxant factors produced by eNOS, allowing the endothelium to regulate smooth muscle tone and proliferation, leukocyte recruitment, and platelet aggregation.…”
Section: Vascular Effectsmentioning
confidence: 99%